Student writing in higher education : new contexts (The Society for Research into Higher Education & Open University Press, 2000)
Academic writing in new and emergent discipline areas. Student writing and staff feedback in higher education. What am I supposed to make of this? The messages conveyed to to students by tutors' written comments. Computer conferencing. Making dances, making essays...